2018
DOI: 10.1021/acs.molpharmaceut.8b00306
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Solid-State Properties and Dissolution Profile of Spray-Dried Ternary Amorphous Solid Dispersions: A Rational Step toward the Design and Development of a Multicomponent Amorphous System

Abstract: The formulation of oral amorphous solid dispersions (ASD) includes the use of excipients to improve physical stability and enhance bioavailability. Combinations of excipients (polymers and surfactants) are often employed in pharmaceutical products to improve the delivery of poorly water-soluble drugs. However, additive interactions in multicomponent ASD systems have not been extensively studied and may promote crystallization in an unpredictable manner, which in turn may affect the physical stability and disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…Therefore, the present study attempts to extent the prior preliminary efforts made for the preparation of an effective APT SD system. Specifically, an in-depth evaluation of the binary SD of APT with Soluplus ® (an amphiphilic copolymer and solubilizer), recently studied by several different research groups [18][19][20][21], with the addition of a surface active compound like Poloxamer 188, a nonionic polyoxyethylene-polyoxypropylene copolymer widely used as an additive in temperature-based SD preparation methods [48,49,[51][52][53], and the preparation of ternary APT-based SD systems, are being evaluated for the first time. One additional advantage of our study is that these solid dispersions have been prepared my melt extrusion procedure, which is a new technique applied in pharmaceutical technology.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the present study attempts to extent the prior preliminary efforts made for the preparation of an effective APT SD system. Specifically, an in-depth evaluation of the binary SD of APT with Soluplus ® (an amphiphilic copolymer and solubilizer), recently studied by several different research groups [18][19][20][21], with the addition of a surface active compound like Poloxamer 188, a nonionic polyoxyethylene-polyoxypropylene copolymer widely used as an additive in temperature-based SD preparation methods [48,49,[51][52][53], and the preparation of ternary APT-based SD systems, are being evaluated for the first time. One additional advantage of our study is that these solid dispersions have been prepared my melt extrusion procedure, which is a new technique applied in pharmaceutical technology.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the present study attempts to extent the prior preliminary efforts made for the preparation of an effective APT SD system. Specifically, an in-depth evaluation of the binary SD of APT with Soluplus ® (an amphiphilic copolymer and solubilizer), recently studied by several different research groups [18][19][20][21], with the addition of a surface active compound like Poloxamer 188, a nonionic polyoxyethylene-polyoxypropylene copolymer widely used as an additive in temperaturebased SD preparation methods [48,49,[51][52][53], and the preparation of ternary APT-based SD systems, are being evaluated for the first time. One additional advantage of our study is that these solid dispersions have been prepared my melt extrusion procedure, which is a new technique applied in pharmaceutical technology.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the amorphous solid powder consists of a chemically homogenous phase in which all components were uniformly mixed at the molecular level. 42 Several studies have suggested that the transformation of the crystalline form of drug to an amorphous form significantly increases its aqueous solubility, dissolution rate, and solid-state stability. 42 In addition, polymers used in the formulation could act as crystallization inhibitors and reduce the particle size, thereby achieving better wettability and preventing recrystallization.…”
Section: Physical State Properties Of Odsfmentioning
confidence: 99%